(untitled) (Heritage, 2021)
Although advances in technology have enabled people to access information almost instantly that would fill their knowledge gaps and improve their skills, or move them away from untruth or half-truth, there are few who do not seek such information. According to the Dunning-Kruger effect, such people are not aware of the deficit of their knowledge, and at the same time they overestimate their abilities. Such personalities, which are characterized by excessive self-confidence, are an integral part of every society. Research has shown that it is difficult to dissuade them in their unsubstantiated beliefs, even when faced with indisputable facts, out of a simple need to defend their self-confidence, but also because they are not aware of their ignorance at all. Also, with their excessive self-confidence, they have the power to exert a strong social influence, because as science has shown, such influence happens on a subconscious level and the reference group more easily adopts their views. In real life or in the digital environment, individuals who are recognized by Dunning and Krieger as incompetent but also overconfident, in their need to impose or defend their views, according to many studies, more vigorously commit one type of contamination from society by half or complete misinformation, without even being aware of it, unlike those who are really experts in certain areas. Such people are often the leaders of many social discussions, from criticism of political candidates, economic analysis, knowledge of virology and the negative effects of compulsory vaccination to analysis of the performance and benefits of luxury brands. The main goal of this paper is to analyze the collected information from the available scientific literature, primarily in the field of marketing communication, psychology, and sociology and to draw the attention of experts dealing with the analysis of consumer behavior to the influence of Danning-Kruger effect on forming or degrading consumer attitudes towards to luxury brands. Knowledge of this phenomenon can help to more accurately create brand communications and more adequately respond to market demands, but also to locate sources of misinformation and respond to them in a timely manner. Negative electronic word-of-mouth communication in the digital environment is a particularly big problem, affecting the image of luxury brands, primarily because digital media have enabled unprofessional individuals to spread untruths without any censorship and thus to some extent reprogram public opinion, or at least some of its parts.